CTD sensor and related bottle data analyses from RRS Discovery cruise DY086 at site P3 - Major, William; Giering, Sarah Lou Carolin; Ainsworth, Joanna; Ashurst, Daniel; Belcher, Anna; Blackbird, Sabena J; Bridger, Martin; Briggs, Nathan; Carvalho, Filipa; Clément, Louis; Cook, Kathryn B; Dumousseaud, Cynthia; et al. (PANGAEA, 2025)
Physical, chemical and biogeochemical measurements derived from CTD-rosette deployments during three visits to site P3 (November to December, 2017) in the South Atlantic. Measurements were made during COMICS cruise DY086 on the RRS Discovery. Physical parameters include temperature, salinity, density, photosynthetically active radiation and turbulence; chemical parameters include dissolved oxygen, dissolved oxygen saturation, nitrate, phosphate and silicate; biogeochemical parameters include turbidity, beam transmittance, beam attenuation, fluorescence, particulate organic carbon (POC), dissolved organic carbon (DOC), chlorophyll-a, net primary productivity (NPP), ambient leucine assimilation and bacterial cell count. To determine turbulence, a downward facing lowered acoustic doppler current profiler (LADCP, Teledyne Workhorse Monitor 300 kHz ADCP) was attached to the CTD frame. Shear and strain, which are obtained from velocity and density measurements, were used to estimate the dissipation rate of turbulent kinetic energy and the diapycnal eddy diffusivity from a fine-scale parameterisation. Estimates are calculated by parameterising internal wave-wave interactions and assuming that wave breaking modulates turbulent mixing. A detailed description of the method for calculating diffusivity from LADCP and CTD can be found in Kunze et al. (2006). Two datasets with different vertical resolutions were produced: one in which the shear is integrated from 150 to 300 m and the strain over 20-150 m, and one in which the shear is integrated from 70 to 200 m and the strain over 30-200 m. Nutrients (nitrate, phosphate, silicate) were determined via colourimetric analysis (see cruise report, Giering and Sanders, 2019), POC was determined as described in Giering et al. (2023), DOC and DOC flux were determined as described in Lovecchio et al. (2023), NPP was determined as described in Poulton et al. (2019), and ambient leucine assimilation and bacterial cell count were determined as described in Rayne et al. (2024). Data was provided by the British Oceanographic Data Centre and funded by the National Environment Research Council.
Keywords: biological carbon pump; fluxes; marine biogeochemistry